PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN TEKSTIL PERIODE 2018-2022 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Khairani, Winda; Mustika, Ita; Laila, Nur Isra; Ferdila, Ferdila; Khadijah, Khadijah (MEASUREMENT : Jurnal Program Studi Akuntansi, 2024)
Increased competition in the manufacturing industry due to the establishment of new companies. They are causing companies to be more concerned with market conditions and prospects so that they can take advantage of opportunities to achieve high profits for the survival and growth of the company. The garment and textile industry has been unstable since the COVID-19 pandemic until the current trend of rising inflation in various countries. This study uses secondary data from the Indonesia Stock Exchange using a quantitative approach. The sample used in this study is the financial statements of textile companies listed on the Indonesia Stock Exchange in 2018-2022 using 8 company populations and 34 company samples selected according to predetermined criteria. Partially cash turnover has a significant effect on profitability. Partially accounts receivable turnover has a significant impact on profitability. Partially inventory turnover does not affect profitability. Cash, accounts receivable, and inventory turnover simultaneously jeopardize the company's profitability. This study aims to provide information to companies on increasing their profitability and to potential new investors who want to invest in textile companies listed on the IDX.